Amphiphilic pentaazamacrocyclic manganese superoxide dismutase mimetics - Lieb, Dominik; Kenkel, Isabell; Miljkovic, Jan; Moldenhauer, Daniel; Weber, Nadine; Filipovic, Milos; Gröhn, Franziska; Ivanovic-Burmazovic, Ivana (Inorganic Chemistry, 2014)
Five newly functionalized pentaazamacrocyclic manganese complexes, with variable lengths and amounts of the aliphatic groups (three compounds with one linear chain containing 12, 16, and 22 carbon atoms, i.e., MnL1, MnL2, and MnL3, respectively, as well as two compounds containing two C12 and C16 chains, MnL4 and MnL5, respectively) that are derivatives of the known SOD mimetic, Mn(Me-Pyane), have been synthesized. These amphiphilic complexes were characterized by the ESI mass spectrometry, potentiometric titrations, light scattering, cyclic voltammetry, and direct stopped-flow determination of their SOD activity at pH 8.1 and 7.4 (in phosphate and HEPES buffers). The formation of supramolecular aggregates that predominantly exist in the solution as a defined micellar/nanostructure assembly, with an average 400 nm size, has been demonstrated for MnL1. The biological effects of the selected complexes (MnL1 and MnL2) on the superoxide level in cytosol and mitochondria have been tested, as well as their effects on the prevention of the lipid peroxidation induced by paraquat. Advantages and disadvantages of the lipophilic pentaazamacrocyclic manganese SOD mimetics in comparison to the corresponding nonsubstituted SOD active complex have been discussed. © 2013 American Chemical Society.

Biochemical insight into physiological effects of H 2S: Reaction with peroxynitrite and formation of a new nitric oxide donor, sulfinyl nitrite - Filipovic, Milos; Miljkovic, Jan; Allgäuer, Andrea; Chaurio Gonzalez, Ricardo Alfredo; Shubina, Tatyana; Herrmann, Martin; Ivanovic-Burmazovic, Ivana (Biochemical Journal, 2012)
The reaction of hydrogen sulfide (H S) with peroxynitrite (a key mediator in numerous pathological states) was studied in vitro and in different cellularmodels. The results show that H S can scavenge peroxynitrite with a corresponding second order rate constant of 3.3±0.4×10 M · s at 23°C (8± 2×10 M · s at 37°C). Activation parameters for the reaction (ΔH‡, ΔS‡ and ΔV‡) revealed that the mechanism is rather associative than multi-step free-radical as expected for other thiols. This is in agreement with a primary formation of a new reaction product characterized by spectral and computational studies as HSNO (thionitrate), predominantly present as sulfinyl nitrite, HS(O)NO. This is the first time a thionitrate has been shown to be generated under biologically relevant conditions. The potential of HS(O)NO to serve as a NO donor in a pH-dependent manner and its ability to release NO inside the cells has been demonstrated. Thus sulfide modulates the chemistry and biological effects of peroxynitrite by its scavenging and formation of a new chemical entity (HSNO ) with the potential to release NO, suppressing the pro-apoptotic, oxidative and nitrative properties of peroxynitrite. Physiological concentrations of H S abrogated peroxynitrite-induced cell damage as demonstrated by the: (i) inhibition of apoptosis and necrosis caused by peroxynitrite; (ii) prevention of protein nitration; and (iii) inhibition of PARP-1 [poly(ADP-ribose) polymerase 1] activation in cellular models, implying that a major part of the cytoprotective effects of hydrogen sulfide may be mediated by modulation of peroxynitrite chemistry, in particular under inflammatory conditions. © The Authors Journal compilation © 2012 Biochemical Society.

Chemical characterization of the smallest S-nitrosothiol, HSNO; Cellular cross-talk of H2S and S-nitrosothiols - Filipovic, Milos; Miljkovic, Jan; Nauser, Thomas; Royzen, Maksim; Klos, Katharina; Shubina, Tatyana; Koppenol, Willem H.; Lippard, Stephen J.; Ivanovic-Burmazovic, Ivana (Journal of the American Chemical Society, 2012)
Dihydrogen sulfide recently emerged as a biological signaling molecule with important physiological roles and significant pharmacological potential. Chemically plausible explanations for its mechanisms of action have remained elusive, however. Here, we report that HS reacts with S-nitrosothiols to form thionitrous acid (HSNO), the smallest S-nitrosothiol. These results demonstrate that, at the cellular level, HSNO can be metabolized to afford NO, NO, and NO species, all of which have distinct physiological consequences of their own. We further show that HSNO can freely diffuse through membranes, facilitating transnitrosation of proteins such as hemoglobin. The data presented in this study explain some of the physiological effects ascribed to HS, but, more broadly, introduce a new signaling molecule, HSNO, and suggest that it may play a key role in cellular redox regulation. © 2012 American Chemical Society.

Generation of HNO and HSNO from nitrite by heme-iron-catalyzed metabolism with H2S - Miljkovic, Jan; Kenkel, Isabell; Ivanovic-Burmazovic, Ivana; Filipovic, Milos (Angewandte Chemie International Edition, 2013)
Taking NO for an answer: A mechanistic study has shown that a heme-iron-catalyzed pathway (see scheme) could lead to the nitrite-/sulfide- induced formation of NO and HNO within mitochondria, and suggests that H S may be the elusive thiol responsible for the reduction of nitrite. This study offers an answer to the decades-old question on the role of nitrite in the treatment of HS poisoning. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

H2S and NO cooperatively regulate vascular tone by activating a neuroendocrine HNO-TRPA1-CGRP signalling pathway - Eberhard, Miriam; Dux, Maria; Namer, Barbara; Miljkovic, Jan; Cordasic, Nada; Will, Christine; Kichko, Tetyana; de la Roche, Jeanne; Fischer, Michael Jochen Marco; Suarez, Sebastian A.; Bikiel, Damian; Dorsch, Karola; et al. (Nature Communications, 2014)
Nitroxyl (HNO) is a redox sibling of nitric oxide (NO) that targets distinct signalling pathways with pharmacological endpoints of high significance in the treatment of heart failure. Beneficial HNO effects depend, in part, on its ability to release calcitonin gene-related peptide (CGRP) through an unidentified mechanism. Here we propose that HNO is generated as a result of the reaction of the two gasotransmitters NO and H 2 S. We show that H 2 S and NO production colocalizes with transient receptor potential channel A1 (TRPA1), and that HNO activates the sensory chemoreceptor channel TRPA1 via formation of amino-terminal disulphide bonds, which results in sustained calcium influx. As a consequence, CGRP is released, which induces local and systemic vasodilation. H 2 S-evoked vasodilatatory effects largely depend on NO production and activation of HNO-TRPA1-CGRP pathway. We propose that this neuroendocrine HNO-TRPA1-CGRP signalling pathway constitutes an essential element for the control of vascular tone throughout the cardiovascular system. © 2014 Macmillan Publishers Limited. All rights reserved.

Improved tag-switch method reveals that thioredoxin acts as depersulfidase and controls the intracellular levels of protein persulfidation - Wedmann, Rudolf; Onderka, Constantin; Wei, Shengwei; Szijarto, Istvan Andras; Miljkovic, Jan; Mitrovic, Aleksandra; Lange, Mike; Savitsky, Sergey; Yadav, Pramod Kumar; Torregrossa, Roberta; Harrer, Ellen G.; Harrer, Thomas; et al. (Chemical Science, 2016)
Hydrogen sulfide (H2S) has emerged as a signalling molecule capable of regulating several important physiological functions such as blood pressure, neurotransmission and inflammation. The mechanisms behind these effects are still largely elusive and oxidative posttranslational modification of cysteine residues (protein persulfidation or S-sulfhydration) has been proposed as the main pathway for H2S-induced biological and pharmacological effects. As a signalling mechanism, persulfidation has to be controlled. Using an improved tag-switch assay for persulfide detection we show here that protein persulfide levels are controlled by the thioredoxin system. Recombinant thioredoxin showed an almost 10-fold higher reactivity towards cysteine persulfide than towards cystine and readily cleaved protein persulfides as well. This reaction resulted in H2S release suggesting that thioredoxin could be an important regulator of H2S levels from persulfide pools. Inhibition of the thioredoxin system caused an increase in intracellular persulfides, highlighting thioredoxin as a major protein depersulfidase that controls H2S signalling. Finally, using plasma from HIV-1 patients that have higher circulatory levels of thioredoxin, we could prove depersulfidase role in vivo.
EVALuna2:13290

Nitric Oxide Is Reduced to HNO by Proton-Coupled Nucleophilic Attack by Ascorbate, Tyrosine, and Other Alcohols. A New Route to HNO in Biological Media? - Suarez, Sebastian A.; Neuman, Nicolas I.; Munoz, Martina; Alvarez, Lucia; Bikiel, Damian; Brondino, Carlos D.; Ivanovic-Burmazovic, Ivana; Miljkovic, Jan; Filipovic, Milos; Marti, Marcelo A.; Doctorovich, Fabio (Journal of the American Chemical Society, 2015)
The role of NO in biology is well established. However, an increasing body of evidence suggests that azanone (HNO), could also be involved in biological processes, some of which are attributed to NO. In this context, one of the most important and yet unanswered questions is whether and how HNO is produced in vivo. A possible route concerns the chemical or enzymatic reduction of NO. In the present work, we have taken advantage of a selective HNO sensing method, to show that NO is reduced to HNO by biologically relevant alcohols with moderate reducing capacity, such as ascorbate or tyrosine. The proposed mechanism involves a nucleophilic attack to NO by the alcohol, coupled to a proton transfer (PCNA: proton-coupled nucleophilic attack) and a subsequent decomposition of the so-produced radical to yield HNO and an alkoxyl radical. (Graph Presented).

Saying NO to H2S - Miljkovic, Jan; Eberhardt, Miriam; Herrmann, Martin; Meßlinger, Karl; Reeh, Peter; Ivanovic-Burmazovic, Ivana; Filipovic, Milos (Nitric Oxide-Biology and Chemistry, 2013)

Working with "H2S": Facts and apparent artifacts - Wedmann, Rudolf; Bertlein, Sarah; Macinkovic, Igor; Böltz, Sebastian; Miljkovic, Jan; Munoz Becerra, Luis; Herrmann, Martin; Filipovic, Milos (Nitric Oxide-Biology and Chemistry, 2014)
Hydrogen sulfide (H2S) is an important signaling molecule with physiological endpoints similar to those of nitric oxide (NO). Growing interest in its physiological roles and pharmacological potential has led to large sets of contradictory data. The principle cause of these discrepancies can be the common neglect of some of the basic H2S chemistry. This study investigates how the experimental outcome when working with H2S depends on its source and dose and the methodology employed. We show that commercially available NaHS should be avoided and that traces of metal ions should be removed because these can reduce intramolecular disulfides and change protein structure. Furthermore, high H2S concentrations may lead to a complete inhibition of cell respiration, mitochondrial membrane potential depolarization and superoxide generation, which should be considered when discussing the biological effects observed upon treatment with high concentrations of H2S. In addition, we provide chemical evidence that H2S can directly react with superoxide. H2S is also capable of reducing cytochrome c(3+) with the concomitant formation of superoxide. H2S does not directly react with nitrite but with NO electrodes that detect H2S. In addition, H2S interferes with the Griess reaction and should therefore be removed from the solution by Cd(2+) or Zn(2+) precipitation prior to nitrite quantification. 2-Phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl 3-oxide (PTIO) is reduced by H2S, and its use should be avoided in combination with H2S. All these constraints must be taken into account when working with H2S to ensure valid data.
EVALuna2:12902